2018
DOI: 10.1002/alr.22171
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 11 inhibits interleukin 10 in B cells of subjects with allergic rhinitis

Abstract: TNF can suppress the expression of IL-10 in B cells via enhancing the expression of HDAC11. Inhibition of HDAC11 restores the IL-10 expression in B cells of AR subjects. HDAC11 may be a novel target for the treatment of AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Results are expressed as mean ± SEM (n 3). the expression of HDAC11 in B cells in a dose-dependent manner (Shao et al, 2018). Our study also indicated that TNF-α can upregulate the protein and mRNA expressions of HDAC11 in HUVECs, while HT-AC decreased HDAC11 protein and mRNA expressions in TNF-α-stimulated HUVECs.…”
Section: Discussionsupporting
confidence: 65%
“…Results are expressed as mean ± SEM (n 3). the expression of HDAC11 in B cells in a dose-dependent manner (Shao et al, 2018). Our study also indicated that TNF-α can upregulate the protein and mRNA expressions of HDAC11 in HUVECs, while HT-AC decreased HDAC11 protein and mRNA expressions in TNF-α-stimulated HUVECs.…”
Section: Discussionsupporting
confidence: 65%
“…Targeting HAT Tip60 inhibits intestinal allergies in a mouse model (10). The expression of HdAc1, HdAc5, HdAc6 and HdAc8 increases in asthmatic mice (11); HdAc11 (12) and HdAc1 (13) expression levels are increased in patients with AR, and HdAc1 also participates in the pathogenesis of childhood asthma (14).…”
Section: Introductionmentioning
confidence: 99%
“…By binding to HDAC1 and the Il10 gene, NFATc1 suppressed B‐cell IL‐10 expression [95]. Shao et al reported higher levels of HDAC11 and lower levels of IL‐10 expression in B cells from allergic rhinitis patients when compared to healthy controls [96]. Introduction of HDAC11 shRNA significantly attenuated murine allergic rhinitis, and HDAC11‐mediated suppression of IL‐10 expression was elicited through HDAC‐mediated deacetylation of c‐Maf, which reduced c‐Maf binding to the il10 locus.…”
Section: Introductionmentioning
confidence: 99%